Strategic Culture, South-South Cooperation, and Soft Power Politics: Explaining Brazilian Foreign Aid - Ramadhan Sasongkojati, R. Moh. Hiu Dilangit; Iman Subono, Nur (JSP (Jurnal Ilmu Sosial dan ilmu Poltik), 2023)
What drives Brazil to provide foreign aid to other developing countries? Historically part of the Global South, its active foreign policy strives to become a global power. While research has highlighted Brazil’s foreign policy objectives in providing aid, such as expanding its diplomatic reputation and exporting its development experience abroad, little has been done to note the strategic properties that motivate the development assistance initiatives. Additionally, the emphasis on South-South Cooperation in Brazil’s aid practice is relevant to the literature on the motives of emerging donors. This article assesses Brazil’s act to provide foreign aid between 2003 and 2016 using the theoretical concept of strategic culture, which refers to the nation’s historical norms and values that inform the strategic act of providing foreign aid. We use primary and secondary data that cover findings from official government sources, policy documents, and academic literature. We argue that cultural elements support the formulation of a foreign policy that seeks to expand Brazil’s influence abroad through development assistance diplomacy. Using foreign aid to counteract its material limits, the goal is to raise Brazil’s stature among developing nations and global affairs and maximize its soft power in the South-focused power structure within the post-Cold War multipolar global order.